I am stuck on a problem, even after finding some similar examples.

The problem: An experiment is successful with probability $p$ and independent of the outcome of all other experiments. When $n$ experiments are done, let $K$ denote the number of failed experiments and let $X$ denote the number of successful experiments until the first failed experiment. What is the joint PMF $P_{K,X}(k,x)$?

From this information, I think I can say that $K$ is binomially distributed and $X$ has a geometric distribution. I have seen examples where the definition of conditional probability is used to find the joint PMF, $P(K=k,X=x)=P(K=k)\cdotp P(X=x|K=k)=P(X=x)\cdotp P(K=k|X=x)$. However, I have no idea how to go from here. $P(K=k)$ and $P(X=x)$ should be easy to find, but I am not really sure how to find either $P(X=x|K=k)$ or $P(K=k|X=x)$. It feels like I am missing some information.

I would appreciate it if somebody could point me in the right direction. I am not really interested in the answer, I just want to know how to tackle this type of problems.

Thank you in advance!


Actually $X$ is not well defined because it is not stated what value it takes if all $n$ experiments succeed.

Let me preassume then that in that case $X$ takes value $n$

So if indeed $X$ takes value $n$ then $K=0$ so that $P(K=0\mid X=n)=1$ and consequently $P(K=k\mid X=n)=0$ for $k\neq0$.

If $X$ takes value $n-1$ then $K=1$ so that $P(K=1\mid X=n-1)=1$ and consequently $P(K=k\mid X=n-1)=0$ for $k\neq1$.

If $X$ takes some value $x\in\{0,1,\dots,n-2\}$ then the $x+1$-th experiment is the first one that fails. After that $n-x-1$ experiments will follow so that $K-1$ has binomial distribution with parameters $n-x-1$ and $1-p$.

That leads to $P(K=k\mid X=x)=P(K-1=k-1\mid X=x)=\binom{n-x-1}{k-1}p^{n-x-1-k}(1-p)^k$.

This all shows that your approach $P(K=k,X=x)=P(K=k\mid X=x)P(X=x)$ might bear fruit.

  • $\begingroup$ Wow, that mostly makes sense to me. Thanks! I already had answer sheets for this exercise so I already knew what should have been the outcome, but it is slightly different from your answer. The answer sheet says $P_{K,X}(k,x)=\binom{n-x-1}{k-1}p^{n-k}(1-p)^k$ under the conditions that $x+k \leq n, x \geq 0, k \geq 0$ and otherwise it is zero. I am confused, is it actually the same because of the conditions added to it? If it is the case, I don't see why they are the same. I am sorry if this should all be very obvious, I do not have to work with probability very often. $\endgroup$ – Jari Aug 2 '17 at 18:51

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.